Acoustic bubbles: Inducing cell interactions via trapping, patterning, and removal - Jonathan Faulkner; Mengren Wu; Madelyn Wicker; Yuan Gao (Sensors and Actuators Reports)
Studying cell-cell interactions is crucial for understanding biological processes and advancing drug development. Recent advancements in microfluidic technology allow cell-cell interaction experiments to be performed on-chip, enabling the study of specific interactions within a highly defined microenvironment. Acoustic bubbles, tiny bubbles excited by an external acoustic source, are clean, biocompatible, and effective tools for manipulating fluids and particles at the microscale. This research presents a novel microfluidic approach using acoustic bubbles to study cell-cell interactions. It focuses on generating, controlling, and removing acoustic bubbles within a microfluidic device to manipulate particles and cells and induce their interaction. In this work, a microbubble is passively generated to separate the channels containing two different types of particles and cells. Under the control of an acoustic field, particles and cells are trapped on either side of the microbubble. The microbubble is then removed to enable interaction between the trapped particles and cells. The impact of channel geometry on bubble stability is quantitatively investigated to optimize the device's performance. Additionally, the successful demonstration of on-chip cell interactions highlights the rapid and straightforward operation of this method. This innovative approach holds great potential for studying specific cell interactions to gain biological insights into disease progression and serves as an effective tool for drug testing.